Intermediate osteotomies in rhinoplasty: a new perspective - Pereira Nunes, D; Tinoco, C; Oliveira E Carmo, D; Paço, J (My University, 2017)
The nasal dorsum framework plays a major role in nasal and facial harmony. This study presents a new approach to an already known technique, intermediate osteotomies, which can be used routinely in patients with cosmetically unpleasant changes in eyebrow-tip line features, allowing the acquisition of a natural, aesthetically agreeable and harmonious dorsum contour, while preserving nasal function. The approach was evaluated retrospectively in 50 consecutive patients at a tertiary referral hospital. Patients were asked to complete a survey to rate their satisfaction with the cosmetic outcome on a 5-point visual analog scale (VAS) and to compare the impact of nasal obstruction on their quality of life, pre- and postoperatively, by completing the validated Nasal Obstruction Symptom Evaluation (NOSE) scale. Satisfaction was scored as excellent (satisfaction level VAS average score, 4.4), with more than 50% of the patients completely satisfied with the aesthetic result, while NOSE scale scores demonstrated preservation of nasal function postoperatively. Typical complications of the upper third of the nose following osteotomies were not observed.
Keywords: Osteotomia; Rinoplastia; Osteotomy; Rhinoplasty